Avaliação da aptidão aeróbia em indivíduos com e sem dor lombar crônica não específica - Fernandes, Isabela Maia da Cruz [UNESP] (2017)
Introduction: The non-specific chronic low back pain (NSCLBP) is the most commonly found in clinical practice as well as being one of the most discussed problems in the world. Individuals with non-specific chronic low back pain (NSCLBP) have a lower level of physical activity when compared with individuals without NSCLBP, and therefore a decrease in aerobic power (V̇O2max). The guidelines of NSCLBP recommend as treatment the practice of physical exercise, as they claim to be effective in reducing the intensity of pain and functional disability. However, studies that use exercise as a treatment for LBP fail to prescribe exercise in a specific way. Objective: Evaluate and compare the effectiveness of different treadmill protocols for aerobic fitness determination in individuals with and without NSCLBP. Materials and Methods: Twenty individuals (10 with NSCLBP and 10 without NSCLBP) underwent two tests (modified Bruce and incremental) on treadmill. The following were collected during the tests: oxygen consumption (V̇O2), heart rate (HR), rate perceived exertion (RPE 6-20), blood lactate concentration ([Lac]), respiratory quotient (RQ) and pain intensity. Independent t-test was used to evaluate the difference between groups. Differences in physiological responses within groups (with and without NSCLBP) and between groups (Group vs. Test Interaction) were analyzed using two-way ANOVA. Statistical significance was set at p < 0.05. Results: When the groups were compared, no differences were observed on age (p-value = 0.839) or HRrest (p-value = 0.730), however the group with NSCLBP was overweight (p-value = 0.031). Only for the respiratory quotient (RQ) variable was observed a main effect of the test (p-value = 0.015) with higher RQ values in the modified Bruce test than in the incremental test. Conclusion: Both tests are good methods for assessing aerobic fitness. However, it can be speculated that using incremental test is a better method for prescribing treatment for this population.